2021
DOI: 10.1080/00036846.2021.1897512
|View full text |Cite
|
Sign up to set email alerts
|

What determines the asset allocation of defined benefit pension funds?

Abstract: The asset allocation decision is one of the most important decisions made by defined benefit pension schemes, with a major effect on the scheme contribution rate, funding ratio and financial position of the sponsoring company. We investigate the determinants of the equity allocation of UK pension funds using a panel of 1,304 observations on 125 companies that were members of the FTSE 100 over the 2003-2019 period. We find that seven variables have a significant effect on the allocation between equities and bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In their panel study, Zhao and Sutcliffe (2021) focused on examining the factors that influence equity allocation in UK pension funds, and reported that scheme maturity, funding ratio, and time trend had the most significant impact on the allocation of assets, particularly equity allocation. Chepkoech et al (2017) conducted a study to examine the factors influencing investment decisions of pension schemes in Kenya, and the findings indicated that the risk-return tradeoff had a significant influence on the investment decisions of pension schemes in Kenya, and that fund managers carefully balance the level of risk associated with investments to ensure optimal returns, while macroeconomic factors such as interest rates, performance of capital markets, and the rate of national economic growth playing a crucial role in shaping the investment decisions of pension schemes.…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In their panel study, Zhao and Sutcliffe (2021) focused on examining the factors that influence equity allocation in UK pension funds, and reported that scheme maturity, funding ratio, and time trend had the most significant impact on the allocation of assets, particularly equity allocation. Chepkoech et al (2017) conducted a study to examine the factors influencing investment decisions of pension schemes in Kenya, and the findings indicated that the risk-return tradeoff had a significant influence on the investment decisions of pension schemes in Kenya, and that fund managers carefully balance the level of risk associated with investments to ensure optimal returns, while macroeconomic factors such as interest rates, performance of capital markets, and the rate of national economic growth playing a crucial role in shaping the investment decisions of pension schemes.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Various factors influence the asset allocation decisions of pension funds, including market trends, investment strategies, regulatory frameworks, governance structures, risk appetite, tax considerations and the availability of domestic assets (Juvonen et al, 2019). The type of retirement scheme also plays a role, as asset allocation for defined benefit (DB) pension funds; for instance, it may depend on factors such as scheme maturity, funding ratio and time trends (Zhao & Sutcliffe, 2021). The basis of asset allocation reflects factors such as familiarity with different asset classes, the development of local capital markets, and the range of investment opportunities available (RisCura, 2020).…”
mentioning
confidence: 99%
“…In their panel study, Zhao and Sutcliffe (2021) focused on examining the factors that influence equity allocation in UK pension funds, and reported that scheme maturity, funding ratio, and time trend had the most significant impact on the allocation of assets, particularly equity allocation. Chepkoech et al (2017) conducted a study to examine the factors influencing investment decisions of pension schemes in Kenya, and the findings indicated that the risk-return tradeoff had a significant influence on the investment decisions of pension schemes in Kenya, and that fund managers carefully balance the level of risk associated with investments to ensure optimal returns, while macroeconomic factors such as interest rates, performance of capital markets, and the rate of national economic growth playing a crucial role in shaping the investment decisions of pension schemes.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The asset allocation of pension funds depends on (among other factors) market trends, investment strategies, regulation and governance structures, risk appetites, tax structures, and the availability of assets domestically (Juvonen et al 2019). Asset allocation may also depend on the type of retirement scheme under consideration-for example, in the case of DB pension funds, asset allocation is dependent on the scheme maturity, the funding ratio, and a time trend (Zhao and Sutcliffe 2021).…”
Section: Asset Base and Asset Allocationmentioning
confidence: 99%